Reporting Guidelines in Implementation Science: Overview, Categorization and Future Directions - CHEN Xiaoshan; WU Dadong; WANG Run; ZHAO Qing; LIU Siyuan; HUANG Wanqing; HUANG Zizhen; WAN Yuting; HU Huanyu; ZHU Junlin; CHEN Jiangyun; HUANG Zhiwei; et al. (Xiehe Yixue Zazhi)
Reporting guidelines are structured checklists for researchers to follow when reporting specific types of studies. As researches conducted in real-world settings to address practical issues, implementation research has stringent requirements for the replicability of result and the transparency of reporting, making its reporting guidelines particularly important. This paper systematically introduces the reporting guidelines in the field of implementation science, outlines their classification systems and scopes of application, and focuses on explaining the core characteristics and functions of five key reporting guidelines, including the Standards for Reporting Implementation Studies (StaRI), Reporting guidelines for implementation and operational research, the Template for Intervention Description and Replication (TIDieR), the Framework for Reporting Adaptations and Modifications-Enhanced (FRAME), and recommendations for specifying and reporting implementation strategies. Furthermore, combined with the PEDALs research paradigm in implementation science, this paper further clarifies the specific application pathways for reporting guidelines and discusses directions for refinement, aiming to provide references for researchers to select appropriate reporting guidelines.